Una aplicación de un modelo neoclásico DSGE con política fiscal. (2012)
We use a Dynamic Stochastic General Equilibrium (DSGE) model to evaluate the effect of supply (productivity) and demand (foreign trade) shocks on the economy. In addition, this paper analyzes the impact of policies, specifically the effect of public spending under given economic environments. Our results show that, in an open economy model, an expansionary policy of public spending increases employment and production in the short run, but carries an additional future cost, which appears to be greater than the short term benefit.